2018
DOI: 10.1038/s41366-018-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protocatechuic acid on insulin responsiveness and inflammation in visceral adipose tissue from obese individuals: possible role for PTP1B

Abstract: PCA restores the insulin responsiveness of OB-VAT by increasing IRS-1 and Akt phosphorylation which could be related with the lower PTP1B activity found in PCA-treated OB-VAT. Furthermore, PCA diminishes inflammation in VAT. These results support the beneficial role of an anthocyanin-rich diet against inflammation and insulin resistance in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…PCA exerted positive regulation of PI3K/AKT and glucose uptake through GLUT4 translocation . PTP1B activity reduction was also shown in AT after in vivo treatment with PCA …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…PCA exerted positive regulation of PI3K/AKT and glucose uptake through GLUT4 translocation . PTP1B activity reduction was also shown in AT after in vivo treatment with PCA …”
Section: Discussionmentioning
confidence: 80%
“…Long‐term cocoa supplementation reduced adipose tissue inflammation in high‐fat‐fed mice by down‐regulating NF‐κB gene expression and modulating eicosanoid metabolism . PCA has been associated with an increase in adiponectin secretion in obese subjects . Likewise, theobromine could be exerting anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with Gallic acid on db/db mice and fructoseadministered rats facilitated glucose homeostasis, improved insulin sensitivity, reduced obesity, reduced elevated blood pressure and decreased cholesterol levels, as well as inducing adipogenesis in 3T3-L1 adipocytes (Variya et al, 2019). A strong body of evidence supports the biological activity in vitro of Protocatechuic acid as an antioxidant and insulin-mimetic molecule in different biological models (Ormazabal et al, 2018).…”
Section: Identification and Quantification Of Phenolic And Heterocyclmentioning
confidence: 93%
“…Indeed, such metabolites derived from anthocyanins have also been shown to have biological properties against diabetes. The effect of protocatechuic acid (PCA) in the chronic inflammation in visceral adipose tissue (VAT) that may lead to insulin resistance and T2DM was evaluated [ 183 ]. The results showed that this metabolite restored the lack of insulin response in the obese-VAT individuals, by increasing the phosphorylation of key factors for insulin sensitivity, such as IRS-1 and Akt, which may be due to the inhibition of protein tyrosine phosphatase 1B activity, a well-known insulin signaling regulator.…”
Section: Why Anthocyanins?mentioning
confidence: 99%